Study of innocent murmurs in children by intracardiac phonocardiography - Ertuğrul, Ali (The Turkish Journal of Pediatrics, 1962)
Innocent murmurs in children occur sufficiently frequently to make their accurate diagnosis of prime importance to the pediatrician, general practitioner and cardiologist. Intracardiac-phonocardiography provides a safe and effective method for making possible a differential diagnosis for innocent murmurs and heart disease. Experiments in ten children and in dogs using phonocardiography have shown that innocent murmurs are produced in the main pulmonary artery. They are heard best at the left of the sternum, in the second, third and fourth intercostal spaces. The sounds are soft and are not transmitted to the left axillary area. They occupy the first two-thirds of the systole. Innocent murmurs have the character of low frequency and amplitude and they never go into the second heart sound. There is no increase in either the first sound or the second sound.